The labor market effects of drug-related violence in a transit country - Ham, Andrés,Ruiz, Juanita (IZA - Institute of Labor Economics, 2024)
We estimate the effects of drug-related violence on individual labor market outcomes in a transit country. Transit countries do not have enough market power to determine the global supply or demand of drugs yet must deal with the consequences from drug trafficking activities. We implement a Bartik-type instrumental variables strategy which assumes that violence in Honduran municipalities located along drug transport routes changes when coca production in Colombia grows or contracts. Our results show that drug-related violence has negative effects on extensive and intensive margin labor market outcomes for transit country workers and has greater effects on women than men.
10419/302643
Keywords: Graue Literatur; drug markets; violence; labor market outcomes; gender inequality; instrumental variables